Social Solidarity of Javanese Society in Seven Villages of Modayag District - Syah, Ilham (Kawanua International Journal of Multicultural Studies, 2023)
This research is oriented towards discussing Durkheim's social solidarity in the transmigrant society in the seven Villages in Modayag District, East Bolaang Mongondow Regency. This study uses a qualitative descriptive method with fourteen informants. The technique of determining informants is purposive sampling. The research instruments are the researchers themselves and the data analysis techniques include data reduction, data display, data verification. Based on the results of the study, it was found that the social solidarity built in the Javanese society in the seven Villages in Modayag is in the form of organic solidarity according to Durkheim's theory. Mechanical solidarity is the solidarity built because of the art and cultural values jointly adhered to in society or societies that are still homogeneous in nature. In the Javanese society in the seven Villages in Modayag District, East Bolaang Mongondow Regency, religious values, language, art and culture are maintained even though the transmigrant society lives amidst the indigenous Mongondow culture and other tribes such as Minahasa, Gorontalo and Sanger. However, Javanese culture has become a collective value that can influence the surrounding community. The Javanese society in the seven Villages in Modayag interacts with various cultures, tribes and religions, but the rooted Javanese religious values, language and art culture are maintained and give birth to a collective conscience among the Javanese people which becomes a symbol of their social solidarity.